PENGARUH DISIPLIN GURU EKONOMI TERHADAP HASIL BELAJAR SISWA DI SMA PGRI 1 PONTIANAK - Apriadi, Bayu; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of the discipline of economic subject teachers on student learning outcomes in class X SMA PGRI 1 Pontianak academic year 2016/2017 ". The method used in this study is an associative method with a form of expositional research. The population in this study were 59 students with class X as many as 51 students. For data collection using direct communication techniques (interview guidelines), indirect communication techniques (teacher economic discipline questionnaire), and documentary study techniques (student test score data). The results of this study indicate that there is a positive influence on the discipline of teachers of economic subjects on student learning outcomes in class X SMA PGRI 1 Pontianak academic year 2016/2017. This can be seen from the value of t count of 6.654 which shows that there is an influence of teacher discipline on student learning outcomes. When compared with the value of t table with a 0.05 level of significance of 2.010 so that Ha is accepted. The conclusion of this study is the discipline of teachers of economic subjects have a significant influence on student learning outcomes in class X SMA PGRI 1 Pontianak academic year 2016/2017. Keywords: Teacher discipline, learning outcomes.